IN BRAIN POST-ISCHEMIC PLASTICITY, Na+/Ca2+ EXCHANGER 1 AND Ascl1 INTERVENE IN MICROGLIA-DEPENDENT CONVERSION OF ASTROCYTES INTO NEURONAL LINEAGE. (July 2022) - Casamassa, Antonella; Cuomo, Ornella; Pannaccione, Anna; Cepparulo, Pasquale; Laudati, Giusy; Valsecchi, Valeria; Annunziato, Lucio; Pignataro, Giuseppe
Highlights: Post-ischemic astrocyte-microglia crosstalk elicits the co-expression of Ascl1 and NCX1 in striatal anoxic astrocytes. The reoxygenation of anoxic astrocytes with the conditioned medium derived from IL-4 stimulated microglia strongly promotes the astrocytic co-expression of Ascl1 and NCX1. Ascl1 expression in striatal anoxic astrocytes depends on NCX1 since its silencing prevents Ascl1 expression both in in vitro and in post-ischemic ex vivo experimental conditions. Abstract: The intricate glia interaction occurring after stroke strongly depend on the maintenance of intraglial ionic homeostasis. Among the several ionic channels and transporters, the plasmamembrane Na + /Ca 2+ exchanger (NCX) represents a key player in maintaining astroglial Na + and Ca 2+ homeostasis. Here, using a combined in vitro, in vivo and ex vivo experimental strategy we evaluated whether microglia responding to ischemic injury may influence the morphological and the transcriptional plasticity of post-ischemic astrocytes. Astrocyte plasticity was monitored by the expression of the transcription factor Acheate-scute like 1 (Ascl1), which plays a central role in the commitment of astrocytes towards the neuronal lineage. Furthermore, we explored the implication of NCX1 expression and activity in mediating Ascl1-dependent post-ischemic astrocyte remodeling. We demonstrated that: (a) in astrocytes co-cultured with microglia the exposure to oxygen and glucose deprivation followed by 7 days of reoxygenation induced a prevalence of bipolar astrocytes overexpressing Ascl1 and NCX1, whereas this did not occur in monocultured astrocytes; (b) the reoxygenation of anoxic astrocytes with the conditioned medium derived from IL-4 stimulated microglia strongly elicited the astrocytic co-expression of Ascl1 and NCX1; (c) Ascl1 expression in anoxic astrocytes was dependenton NCX1 since its silencing prevented Ascl1 expression both in in vitro and in post-ischemic ex vivo experimental conditions. Collectively, the results of our study support the idea that, after brain ischemia, astrocyte-microglia crosstalk can influence astrocytic morphology and its Ascl1 expression. This phenomenon is strictly dependent on ischemia-induced increase of NCX1 which in turn induces Ascl1 overexpression possibly through astrocytic Ca 2+ elevation. Graphical Abstract: Image, graphical abstract